Intensities of quantum transitions in hexagonal nanotubes within the exciton spectral range - Makhanets, O.M.; Tsiupak, N.R.; Voitsekhivska, O.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2012)
The theory of exciton spectrum and intensities of interband quantum transitions in multi-shell hexagonal semiconductor nanotube is developed within the effective masses and rectangular potentials approximations using Bethe variational method. The obtained theoretical results well explain the experimental position of luminescence peak for GaAs/AlxGa₁-xAs nanotubes.